Radiofrequency Ablation in Chondroblastoma of the Femoral Headin Skeletally Immature Individuals: A Case Report - Pornwattanavate, Samatit; Arpornchayanon, Olarn; Luevitoonvechkij, Sirichai; Pruksakorn, Dumnoensun (The Bangkok Medical Journal, 2017)
Surgical management of chondroblastoma of the femoral head in skeletal immaturityis challenging due to difficult access and a risk of epiphyseal plate injury. A 13-year oldboy presented with left hip pain and limping for over 1 year. Based on imaging andpathology report, chondroblastoma was diagnosed. The size of the tumor was 1.7 cmin diameter. To avoid epiphyseal plate and articular damage, percutaneous radiofrequencyablation was performed under fluoscopic guidance with a 70o Celsius monopolar probefor 3 minutes’ duration repeated 3 times. The 2nd ablation procedure was performedafter 3 months to minimize risk of recurrence. The pain had subsided at the 3 monthsfollow up. Over the 4 years follow up period, this case shows good functional outcomewithout deformity of the femoral head or tumor recurrence.